Operating Theatres: Study of Unidirectional Flow Ventilation- Conditions for microbiological air cleanliness during advanced surgeries - Nava, Alessandro (My University, 2019)
Design of a heating, ventilating and air conditioning (HVAC) system for an operating room is aimed at preventing the risk of infections during surgical operations while maintaining an adequate comfort condition for the patient and the surgical staff. One of the key elements to ensure the OT (operating theatre) cleanliness is the control of the airborne microbiological contaminants in the room through the air ventilation system, equipment and medical staff routine. Generally, in OT two types of air ventilation systems are mainly adopted: turbulent system, which mixes all the air volume of the operating room following the dilution principle concept; and the unidirectional airflow (UDF) ventilation system, which concentrates all the airflow over the sterile zone. The idea of UDF system is to sweep away the dirtiness present in the sterile zone and to avoid disturbances or entrainment of contaminated particles from the external dirty zone. The aim of this Master Thesis is to study more in details UDF ventilation system by means of UFP (Ultrafine Particles) and CFU (Colony Forming Unit) concentration measurements performed during different types of advanced real surgeries in two different hospitals in Sweden. The common hospital type of technical gowning available inside the OT are: the single use type with high performances and the ordinary scrub suit, more comfortable but less performing in the particles retention from the staff. Therefore, there are two main types of protection for the diffusion of airborne particles: technical clothing systems and the air ventilation technology. The deployment of low performance technical clothing allows a more direct testing of the UDF capacity to keep the surgery table area clean. Furthermore, the current standards do not make a clear distinction between the air distribution systems used and their cleaning capacity over the cleaning table. According to the standards, sterile area protection mostly depends upon the technical gowning quality, and the use of less performing technical clothing leaves the ventilation system as key determinant of contamination control. The airborne samples collected during the surgeries data collection allowed new scenarios in this field, also due to the small number of available studies and data in the literature. The experimental values measured have shown the UDF’s capacity to ensure a high degree of cleanliness on the surroundings of the surgery table. Despite the use of less performing technical clothing, the UDF ventilation system can keep the surgical area safe throughout all the surgery routine. Furthermore, this work defines an outlook over the specific positions required for the optimal measurement campaign. Moreover, the amount of measurements allows an understanding of the weak points of the UDF ventilation system in combination with medical procedures, especially during the medical staffs shift changes.
Keywords: Operating theatres; Unidirectional airflow; LAF; UDF; Ultrafine particles; Colony Forming Units; CFU